If it's not what You are looking for type in the equation solver your own equation and let us solve it.
10y+3=12y-3
We move all terms to the left:
10y+3-(12y-3)=0
We get rid of parentheses
10y-12y+3+3=0
We add all the numbers together, and all the variables
-2y+6=0
We move all terms containing y to the left, all other terms to the right
-2y=-6
y=-6/-2
y=+3
| .99x=100 | | 24+5t=184 | | 2x^2+15x-30=46 | | 2x^2+15x-30=23 | | 13=4+3(t+2) | | 2a+-4=10 | | 7x²-5x=0 | | 4y3-40y=0 | | X²(2x+1)(x-3)=0 | | 5x=1236(7) | | 7x-6=10x+9 | | 5+x3=17 | | 0.2x-3=x+0.2 | | B+24=4b | | X²+10x-2=0 | | 2(3–2x)=3(x–5)x= | | 2(3–2x)=3(x–5) | | 2x/3+6=3x/5+8xकेमानकेलिएदियेगयेसमीकरणकोहलकीजिये | | -a128=64 | | 4/15-2/5=x-5/3 | | 5x-9=12-4x-8 | | 2x(3)/2-3x=0 | | 11x/2-10x-9=0 | | X/3+x+5/2=0 | | 8x+16+24=0 | | 2(1/2x-5=25 | | 5y/2y-1=2 | | 4x+5-2=19 | | 4-x=185 | | 7y+5=30 | | 5x+7=82° | | 2^(0.9x)=1379 |